X-Ray CT Investigation on Fractal Characteristics of Fine-Grained Tailing Sand in Fujian's Makeng: Insight into the Mesoscopic Seepage Failure. (21st December 2021) - Long, Dayu; Li, Changhong; Wang, Yu; Shi, Yueqi
Abstract : This work is aimed at revealing the mesophysical process and mechanical behaviors of fine-grained tailing sand during seepage failure. The macroscopic seepage tests combined with posttest X-ray computed tomography (CT) were employed to study the fractal characteristics of mesostructure. Results show that before and after the seepage failure of fine-grained tailing sand, fractal of pore distribution (D pd ) and fractal dimension of pore size (D ps ) show a relatively obvious positive correlation with porosity. Tailing particles migrate along the seepage direction during the seepage process, resulting in the gradual decrease of D pd and pore distribution area. The D ps reflects the variation characteristics of pore number distribution with different pore sizes. The increase in D ps leads to a decrease in the uniformity of pore size and an increase in the size difference between pores. The mass fractal dimension (D m ) of fine-grained tailing sand samples ranges from 1.6472 to 1.8256. With the increase of D m, the coefficient of uniformity (C u ) of tailing sand tends to increase. The D m method can discern the seepage failure type of fine-grained tailing sand, and it is more accurate than the traditional method. This study provides a reference for the prevention and control of the seepage failure of tailing dam.